Art for bugs: 'cultured' microorganisms. Issue 1 (December 2013) - Alexander, Stefanie-Ann; Sloggett, Robyn; Schiesser, Carl H
Abstract : Aesthetic and structural damage can occur to culturally significant objects as a result of the growth and activities of communities of microorganisms known as biofilms. Referred to as 'biodeterioration', this process embodies a complex series of interactions that in many cases are accelerated by temperature and humidity. Bacteria growing in biofilms are able to undergo controlled and synchronised dispersal events where sessile biofilm cells convert to free-swimming, planktonic bacteria [1]. The free radical nitric oxide (NO) is used widely as a signalling molecule and has been identified as an elicitor of biofilm dispersal through the initiation of oxidative/nitrosative stress conditions. This paper investigates various nitroxides (which are more stable free radical species) and demonstrates the ability of some nitroxides to behave like NO.